## Lakshya Education MCQs

Question:

If the number 5 * 2 is divisible by 6, then * = ?

Options:
 A. 2 B. 7 C. 3 D. 6

Replacing * by x
5 x 2 is divisible by 2 (Reference : Divisibility by 2 rule)
For 5 x 2 to be divisible by 3, 5 + x + 2 shall be divisible by 3 (Reference : Divisibility by 3 rule)
=> 7 + x shall be divisible by 3
=> x can be 2 or 5 or 8
From the given choices, answer = 2

Not understood this question clearly
Date : 2018-09-30 02:51:23

Shark khan

Date : 2017-12-28 23:00:08

Pranjal more

Very nice
I love it

Date : 2017-10-15 04:52:10

Earn Reward Points by submitting Detailed Explaination for this Question

## More Questions on This Topic :

Question 1.

(23341379 x 72) = ?

Options:
1.    1680579288
2.    1223441288
3.    2142579288
4.    2142339288

23341379 x 72 = 23341379(70 + 2) = (23341379 x 70) + (23341379 x 2)
= 1633896530 + 46682758 = 1680579288

Question 2.

$$\frac{(912+643)^{2}+(912-643)^{2}}{(912\times912+643\times643)}$$

Options:
1.    122
2.    2
3.    1
4.    None of these

$$\frac{(912+643)^{2}+(912-643)^{2}}{(912\times912+643\times643)} = \frac{(912+643)^{2}+(912-643)^{2}}{(912^{2}+643^{2})}= \frac{2(912^{2}+643^{2})}{(912^{2}+643^{2})}=2$$

Question 3.

When (6767 +67) is divided by 68, the remainder is

Options:
1.    0
2.    22
3.    33
4.    66

(xn+1) is divisible by (x + 1) only when n is odd

=> (6767 + 1) is divisible by (67 + 1)

=> (6767 + 1) is divisible by 68

=> (6767 + 1) ÷  68 gives a remainder of 0

=> [(6767 + 1) + 66] ÷ 68 gives a remainder of 66

=> (6767 + 67) ÷ 68 gives a remainder of 66
Question 4.

$$\left(1-\frac{1}{n}\right)+\left(1-\frac{2}{n}\right)+\left(1-\frac{3}{n}\right)+... up to n terms = ?$$

Options:
1.    (n−1)
2.    $$\frac{n}{2}$$
3.      $$\frac{1}{2}$$ (n−1)
4.     $$\frac{1}{2}$$  (n+1)

$$\left(1-\frac{1}{n}\right)+\left(1-\frac{2}{n}\right)+\left(1-\frac{3}{n}\right)+... up to n terms$$

= $$\left(1+1+1+... up to rerms \right) - \left(\frac{1}{n}+\frac{2}{n}+\frac{3}{n}+...up to rerms\right)$$

= $$n-\frac{1}{n}\left(1+2+3+...up to rerms\right)$$

= $$n-\frac{1}{n}\left[\frac{n(n+1)}{2}\right]$$

= $$n-\frac{(n+1)}{2}$$

= $$\frac{(2n-n-1)}{2}$$

= $$\frac{n-1}{2}$$

Question 5.

? + 3699 + 1985 - 2047 = 31111

Options:
1.    21274
2.    27474
3.    21224
4.    27224